Assessing Local "Diversity": A Nationally Representative Analysis. (April 2022) - Rajasekar, Neeraj; Stewart, Evan; Gerteis, Joseph
The meanings and definition of "diversity" can change across different applications and contexts, but many such meanings have implications for racial difference and racial ideology in the United States. We provide a nationally representative analysis of how everyday Americans assess "diversity" in their own communities. We test how county-level racial, religious, economic, and political heterogeneity predict the view that one lives in a highly diverse locale; we also test how individual-level factors predict such a view. Among the four indicators of local difference, racial difference is most strongly and consistently associated with Americans' assessments of local diversity. Individual-level factors do not weaken this relationship; rather, local context and individual-level factors conjointly predict assessments of local diversity. Despite the flexible, hyperinclusive nature of diversity discourse, local racial difference is salient in Americans' assessments of "diversity" in their communities, and this pattern is not simply a product of individual-level factors. Our findings illustrate another dimension of the flexible-yet-racialized nature of diversity discourse in the United States. We also show that Americans are particularly aware of racial difference in their locale, which has implications for social and ideological responses to changing communities and a changing nation.